Polyandry Marriage Pattern in Highland People of Nepal - Gyanwali, Gokarna P.; Dhakal, Ram H. (Molung Educational Frontier, 2024)
Polyandry is a pattern of marriage in which a woman has more than one husband. It has been a common practice of marriage around the world since the historical period. There have been various forms of polyandry in Asia, Africa, Europe, Latin America, and America (snowbird of paradise, 2024). Among them, fraternal polyandry is common in most parts of the world. The polyandry system has also been common in most parts of Nepal in various forms. This article describes the present practice and situation of polyandry in the world as well as in the highland region of Nepal. This research is concerned with the study of the practice of polyandry in the upper Mustang of Nepal. For this research, the primary and secondary data are collected from the field and secondary sources like the Rural Municipality chairperson and local people for the case study. The major findings are that polyandry is prevalent in high hill and Himalayan regions of Nepal. It is arranged by the parents of girls or boys due to economic, social, biological, and cultural factors in the Himalayan region of Nepal.